2019
DOI: 10.1371/journal.pone.0223803
|View full text |Cite
|
Sign up to set email alerts
|

BMAL1 associates with chromosome ends to control rhythms in TERRA and telomeric heterochromatin

Abstract: The circadian clock and aging are intertwined. Disruption to the normal diurnal rhythm accelerates aging and corresponds with telomere shortening. Telomere attrition also correlates with increase cellular senescence and incidence of chronic disease. In this report, we examined diurnal association of White Collar 2 (WC-2) in Neurospora and BMAL1 in zebrafish and mice and found that these circadian transcription factors associate with telomere DNA in a rhythmic fashion. We also identified a circadian rhythm in T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 55 publications
(58 reference statements)
0
9
0
Order By: Relevance
“… 80 In addition, a recent study suggests the involvement of BMAL1 in the regulation of telomeric heterochromatin. 81 Unlike BMAL1, which mainly maintains telomeric homeostasis, we found that CLOCK was enriched across diverse genomic repetitive sequences, including LINE1, satellite DNA, and rDNA, thus preventing aging-associated heterochromatin loss. Despite the different mechanisms, these studies collectively demonstrate the noncanonical roles of CLOCK and other core circadian proteins in regulating chromatin homeostasis.…”
Section: Discussionmentioning
confidence: 70%
“… 80 In addition, a recent study suggests the involvement of BMAL1 in the regulation of telomeric heterochromatin. 81 Unlike BMAL1, which mainly maintains telomeric homeostasis, we found that CLOCK was enriched across diverse genomic repetitive sequences, including LINE1, satellite DNA, and rDNA, thus preventing aging-associated heterochromatin loss. Despite the different mechanisms, these studies collectively demonstrate the noncanonical roles of CLOCK and other core circadian proteins in regulating chromatin homeostasis.…”
Section: Discussionmentioning
confidence: 70%
“…Similar outcomes of lifespan were obtained in Drosophila [77]. Park et al found that BMAL1 is associated with telomere length in zebrafish as well as mice; it is characterized by rhythmical binding to the ends of chromosomes, which may lead to the conclusion that the circadian clock components are greatly involved in telomere homeostasis regulation [78]. Moreover, the rhythms in the heterochromatin at the telomeres in zebrafish and mice support this hypothesis [78].…”
Section: Circadian Clock Disturbances and Accelerated Agingmentioning
confidence: 68%
“…Moreover, the rhythms in the heterochromatin at the telomeres in zebrafish and mice support this hypothesis [78]. Furthermore, BMAL1 probably takes part in the rhythmical epigenetics of telomeres and regulates the expression of a long non-coding RNA called telomeric repeat-containing RNA (TERRA), which is implicated in telomere protection by the recruitment of epigenetic factors [78]. BMAL1 -/mice are characterized by premature aging in cases of increased ROS production and cardiac telomere shortening.…”
Section: Circadian Clock Disturbances and Accelerated Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, in another study using the zebrafish brain and the mice liver, a lncRNA Telomeric Repeat-containing RNA (TERRA) was found to be associated with circadian transcription factor BMAL1. Ablation of BMAL1 expression in a mouse model resulted in the disruption of TERRA's diurnal rhythmic expression and H3K9me3-mediated telomeric homeostasis, thus implicating, TERRA and BMAL-1 in aging-related telomeric erosion [108].…”
Section: Role Of Non-coding Rnas In Molecular Clock Regulation: Implimentioning
confidence: 96%